Asymmetric chromosome segregation in Xanthomonas citri ssp. citri - Ucci, Amanda P. [UNESP]; Martins, Paula M. M. [UNESP]; Lau, Ivy F. [UNESP]; Bacci, Maurício [UNESP]; Belasque, Jose; Ferreira, Henrique [UNESP] (Wiley-Blackwell, 2014)
This study was intended to characterize the chromosome segregation process of Xanthomonas citri ssp. citri (Xac) by investigating the functionality of the ParB factor encoded on its chromosome, and its requirement for cell viability and virulence. Using TAP tagging we show that ParB is expressed in Xac. Disruption of parB increased the cell doubling time and precluded the ability of Xac to colonize the host citrus. Moreover, Xac mutant cells expressing only truncated forms of ParB exhibited the classical phenotype of aberrant chromosome organization, and seemed affected in cell division judged by their reduced growth rate and the propensity to form filaments. The ParB-GFP localization pattern in Xac was suggestive of an asymmetric mode of replicon partitioning, which together with the filamentation phenotype support the idea that Xac may control septum placement using mechanisms probably analogous to Caulobacter crescentus, and perhaps Vibrio cholerae, and Corynebacterium glutamicum. Xac exhibits asymmetric chromosome segregation, and the perturbation of this process leads to an inability to colonize the host plant.
Keywords: Cell division arrest; chromosome segregation; citrus canker